2022
DOI: 10.1002/asia.202200550
|View full text |Cite
|
Sign up to set email alerts
|

Mannose‐Decorated Composite Peptide Hydrogel with Thixotropic and Syneresis Properties and its Application in Treatment of Leishmaniasis

Abstract: Leishmaniasis, caused by the intramacrophage protozoan parasite Leishmania donovani, is a life-threatening yet neglected vector-borne disease. Few medications for the treatment of this disease are available. However, targeted delivery of drugs to macrophages remains a significant concern. Macrophages are equipped with many receptors, and therefore putting suitable ligands in the macrophage targeting drug delivery vehicle gained a lot of attention. One such receptor is the mannose receptor, abundantly expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Over the last couple of decades, peptide-based hydrogels have gained increasing attention for biomedical applications and diagnostic research considering their particular properties, such as their biocompatibility, biodegradability, tuneability,hydrophilic-lipophilic balance of the structure, tissue-like elasticity, and non-cytotoxicity [98]. Considering these properties, recently, Dowari and coworkers prepared a mannose-containing composite hydrogel by combining a self-aggregating short peptide (Nap-FFGE-NH 2 ) and a mannosecontaining non-aggregating peptide (Nap-FF-mannosyl) [99]. Nap-FF is a small peptide hydrogelator that can form versatile biofunctional nanofibrous structures [100].…”
Section: Mannosylated Peptides and Proteinsmentioning
confidence: 99%
“…Over the last couple of decades, peptide-based hydrogels have gained increasing attention for biomedical applications and diagnostic research considering their particular properties, such as their biocompatibility, biodegradability, tuneability,hydrophilic-lipophilic balance of the structure, tissue-like elasticity, and non-cytotoxicity [98]. Considering these properties, recently, Dowari and coworkers prepared a mannose-containing composite hydrogel by combining a self-aggregating short peptide (Nap-FFGE-NH 2 ) and a mannosecontaining non-aggregating peptide (Nap-FF-mannosyl) [99]. Nap-FF is a small peptide hydrogelator that can form versatile biofunctional nanofibrous structures [100].…”
Section: Mannosylated Peptides and Proteinsmentioning
confidence: 99%
“…Heli et al [274] investigated the effect of ligand modification of PM-loaded chitosan NPs on their anti-leishmanial activity and found the mannosylated formulation to be a suitable targeted drug delivery system for uptake into Leishmania-infected macrophages without any cytotoxic activity. Similarly, Das et al [275] prepared a mannose containing composite hydrogel loaded with AmB and showed it to be a suitable candidate for the treatment of leishmaniasis due to its injectability, biodegradability, non-cytotoxicity and efficient drug delivery properties.…”
Section: Protozoan Infectious Diseasesmentioning
confidence: 99%
“…19 These peptide gelators form hydrogels with micro-and nanofibril network structures under appropriate conditions through the selfassembly of individual molecules by using various noncovalent interactions including hydrogen bonding, p-p interactions, van der Waals interactions, hydrophobic interactions and others. [20][21][22][23][24] These hydrogels have a wide range of applications in the biomedical field, such as sustained release of drugs and important biomolecules, [25][26][27][28] drug delivery, 25,29 cell culture, 27 tissue engineering, 1,29 wound healing, 19,32 and antimicrobial, [30][31][32][33][34][35][36][37][38][39][40] antiparasitic 37,42 and anticancer agents. [41][42][43][44][45][46][47][48] The self-assembled nanostructures show a remarkably increased bioactivity compared to the unassociated peptide molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, antibacterial resistance is a primary concern due to inappropriate and irrational use of antibiotics. 38,39 The development of new antibiotics is quite expensive and time-consuming. To overcome these issues, antimicrobial peptides (AMPs) are chosen as promising agents for combating bacterial resistance.…”
Section: Introductionmentioning
confidence: 99%